Zakaria Paliashvili Street In Kutaisi - Kezevadze, Merab (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
Old districts of Kutaisi are situated on both banks of the river Rioni. Modern city center - Boulvoire and dramatic theatre surroundings are mentioned in the late feudal age. Mentioning Paliashvili street starts from XIX century. The street used to start from the red bridge and ended to the east line of the present-day square. In 60 meters from the bridge the street had 2 turning points, one was heading right (modern Rustaveli square) second was going on the left side towards Chain bridge. Paliashvili street passage from the cross of St. Nino street to the west side there were generally single-story houses which were developed into 2 and 3 floored houses though there are several exceptions, e.g. Begov house built in 1881, also a former culture house which still holds the same name. From the old buildings situated in Paliashvili street only some of them survived till this time, we should distinguish Kutaisi Public Library building among them. Initially, it was the property of the noble person Stefane Akopashvili. In 1875 it was the house of the local government. In 1890 the house was bought by Aron Eligulashvili. The library which was the inheritor of the one founded by Anton Lortkipanidze in 1873 took the building in 1934. Despite lots of, sometimes incorrect reconstructions Zakaria Paliashvili street retains initial distinctness and beauty, which is mostly provided by its situation (closeness of Boulvoire and the bridge).